If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3(-3 + 3x) = 11 x + (-3 * -3 + 3x * -3) = 11 x + (9 + -9x) = 11 Reorder the terms: 9 + x + -9x = 11 Combine like terms: x + -9x = -8x 9 + -8x = 11 Solving 9 + -8x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -8x = 11 + -9 Combine like terms: 9 + -9 = 0 0 + -8x = 11 + -9 -8x = 11 + -9 Combine like terms: 11 + -9 = 2 -8x = 2 Divide each side by '-8'. x = -0.25 Simplifying x = -0.25
| 2x-3(x+1)=-2(x-1) | | (13t+7)(6t+-5)=0 | | 3x^2-0.2x+0.0024=0 | | 2/x+2/7x=2 | | (m+2)/3+(m-2)/5=4 | | x-4+2y=0 | | x-2(2)+-1y=0 | | x-2(2)+-1y= | | x-4+2x=0 | | U-4=sqrt(-5U+70) | | 3(x+7)-6x=3(x+9) | | 49.5*x=8.25 | | 3(1+y)+y=-9 | | -0.5+0.25= | | 8.25*x=8 | | -8(-0.5+0.25y)+y=3 | | 2(-4.2+y)-3y=-9 | | 4(-3+2y)-3y=8 | | 14x+6y=180 | | 2x^2-17x+128=0 | | 11-4x=-7x+5 | | 5/8(X-6)=2+4X | | 5x^2-16x-12=0 | | 47.5=9.5 | | 9.5=47.5 | | 81-9= | | -76=26m | | -24(3)-4= | | 2*x^2-7*x-15=0 | | 5x^2-18x-21=0 | | y+7-6= | | 21-3(4-1)= |